PENGARUH KONSELING KELOMPOK RASIONAL EMOTIVE TERHADAP KEPERCAYAAN DIRI SISWA KELAS VIII MTs NEGERI SUBAH KABUPATEN BATANG TAHUN PELAJARAN 2013/2014 - Meiningsih, Tri; ., Suhendri (EMPATI, 2014)
Background of this study is the low confidence eighth grade students of MTs Negeri Subah. Goals to be achieved in this study was to determine the effect of group counseling on the self-confidence of rational emotive eighth grade students of MTs Negeri Subah 2013/2014 academic year.The problems revealed in this research is how rational emotive group counseling services affect the confidence of the students? Goals to be achieved in this research is to find out how enfluence rational emotive group counseling on self-confidence eighth grade students of MTs Negeri Subah 2013/2014 academic year. The study was conducted in MTs Subah. The study population of 200 students, which is experiencing problems because confidence is taken only 10 students in the low category pretest results, and then at the interview so that the samples are 10 students, while the sampling technique using purposive sampling. The research instrument is the confidence scale that has been tested for validity and reliability.The design of this study used a quasi-experimental type of experiment with one group pre-test post-test design. The collected data were analyzed using descriptive analysis, and statistical techniques Wilcoxon sign test with a significance level of 5% The results of the analysis obtained t (55)> t table (8) with a 5% significance level, the goal of these studies has been reached, namely that the results of this study have managed to find out how enfluence Rational Emotive Group Counseling Students Against confidence Class VIII MTs Subah 2013/2014 academic year ".Keywords: Rational Emotive Group Counseling, Self-Confiden